The influence of platinum surface oxidation on the performance of a polymer electrolyte membrane fuel cell—probing changes of catalytically active surface sites on a polycrystalline platinum electrode for the oxygen reduction reaction. Issue 3 (14th October 2021) - Eckl, Maximilian Johann; Mattausch, Yannick; Jung, Christoph Karsten; Kirsch, Sebastian; Schmidt, Lasse; Huebner, Gerold; Mueller, Jonathan Edward; Kibler, Ludwig Alfons; Jacob, Timo
Abstract: To obtain fundamental insights into the performance of polymer electrolyte membrane (PEM) fuel cells, we perform a parallel investigation of the influence of platinum surface oxide (PtO) formation on the electrocatalytic activity toward the oxygen reduction reaction (ORR) for a polycrystalline platinum electrode in comparison with a commercial PEM fuel cell. PtO is formed by holding both systems at a constant potential for a given period of time. Conditioning potentials between 0.5 and 1.0 V versus SHE and conditioning times from 5 s up to 10 h are explored, respectively. We find that the voltage difference of the ORR between the oxidized and oxide‐free states depends on both the conditioning potential as well as the conditioning time at a given potential and furthermore increases with the applied target current. The change of the voltage loss over time, the so‐called voltage loss rate α, shows a maximum at potentials between 0.85 and 0.9 V and increases with increasing current density. We discuss various hypotheses to explain these findings obtained by linear voltammetry, Tafel slope analysis, Auger electron spectroscopy, and atomic force microscopy experiments. Finally, we conclude that the voltage loss rate is influenced by changes in the relative electrocatalytic activity of different crystal facets for the ORR as the oxide coverage varies.